Analisis Pengaruh Harga Promosi Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Di Kevin Salon Kalabahi Kabupaten Alor (Studi Kasus Pada Kevin Salon Kalabahi Kabupaten Alor) - Duka, Meriana; Maruli, Elia; Awang, Mesak Y.; Anigomang, Ferdinand Romelus (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is quantitative research with data collection techniques, namely observation, interviews, questionnaires, and documentation studies. This study used primary population data and a sample of 30 Kevin Salon. The statistical method used in this study is multiple linear regression by looking at the significant value of the t test and the significant value of the F test as a benchmark in taking hypotheses and data management results using the help of the IMB Spss 25 For Windows program. The results of this study show that: price has a positive effect on consumer satisfaction with statistical tests through t tests with a real level of 5% which has a probability value of 0.000 < 0.05 this means that price variables have a positive effect on consumer satisfaction. Promotion has a positive effect on consumer satisfaction with statistical tests through t tests with a real level of 5% which has a probability value of 0.001 < 0.05, this means that the promotion variable has a positive effect on consumer satisfaction. Service quality has a positive effect on customer satisfaction with statistical tests through t tests with a real level of 5% which has a probability value of 0.001 < 0.05, this means that service quality variables have a positive effect on customer satisfaction. Price, promotion, and service quality have a positive effect on customer satisfaction with statistical tests through F tests with a real level of 5% which has a probability value of 0.000 <0.05 this means that the variables of price, promotion, and service quality simultaneously affect customer satisfaction.